Brain Innate Immune Response in Diet-Induced Obesity as a Paradigm for Metabolic Influence on Inflammatory Signaling - Macedo, Felipe; dos Santos, Lucas Souza; Glezer, Isaias; da Cunha, Fernanda Marques (Frontiers in Neuroscience, 2019)
Obesity is a predisposing factor for numerous morbidities, including those affecting the central nervous system. Hypothalamic inflammation is a hallmark of obesity and is believed to participate in the onset and progression of the obese phenotype, by promoting changes in neuronal functions involved in the control of metabolism. The activation of brain immune cells in the hypothalamus, which are represented by microglia and brain macrophages, is associated with obesity and has been the focus of intense research. Despite the significant body of knowledge gathered on this topic, obesity-induced metabolic changes in brain cells involved in innate immune responses are still poorly characterized due, at least in part, to limitations in the existing experimental methods. Since the metabolic state influences immune responses of microglia and other myeloid cells, the understanding and characterization of the effects of cellular metabolism on the functions of these cells, and their impact on brain integrity, are crucial for the development of efficient therapeutic interventions for individuals exposed to a long-term high fat diet (HFD). Here we review and speculate on the cellular basis that may underlie the observed changes in the reactivity and metabolism of the innate immune cells of the brain in diet-induced obesity (DIO), and discuss important points that deserve further investigation.